Alérgenos y su influencia en la aparición de rinitis alérgica en niños de 1 a 5 años. Centro Materno Infantil Enrique Ponce Luque Babahoyo Los Ríos octubre 2018 a abril 2019 - Cruz Santillan, Henrry David (2019)
Introduction.- Allergic diseases are the most frequent chronic diseases in the pediatric age. Allergic rhinitis is part of the "allergic march" during childhood. It is one of the most recurrent pathologies in pediatric practice, considering it a global public health problem, it is defined, clinically, as an inflammatory disease of the nasal mucosa mediated by immunoglobulin (IgE) Objectives.- Study with the objective of determining the influence of allergens to allergic rhinitis in children under 1 to 5 years old with acute respiratory infections who come to the Enrique Ponce Luque Mother and Child Center in the city of Babahoyo, to contribute to the quality of attention Methodology.- In this study, an inductive-deductive methodology was used in a descriptive-explanatory-type study with a cross-sectional design, using the survey technique and as an instructive questionnaire for pre-elaborated questions. Results.- In this research, 123 boys and girls with rhinitis were found in a finite population of 181 children, there is a prevalence of 100 boys in the age group of 48 to 60 months, and mothers' knowledge of allergens their signs and symptoms. in 50% of the interviewees. Conclusions.- Lack of knowledge of the mothers participating in the techniques of respiratory therapy as a necessary complement in the medical treatment of respiratory problems in pediatrics